Description of Nemophora acaciae sp. nov. (Lepidoptera: Adelidae) from Kenya - Agassiz, David J. L.; Kozlov, Mikhail V. (Zootaxa, 2015)
Nemophora acaciae sp. nov. is described from Kenya on the basis of a large series bred from flowers of Acacia seyal and A. lahai. The new species differs from all Afrotropical Nemophora species by its dark brown forewing fascia with white medial stripe near the costal margin of forewing. The key to the Afrotropical Nemophora species is provided.